Implementasi E-Commerce CMS Prestashop Sebagai Upaya Strategi dalam Meningkatkan Indeks Penjualan Esteh Indonesia di Jalan Jendral Ahmad Yani Rantauprapat - Akbar Madyan; Syaiful Zuhri Harahap; Rizky Maulana (Universitas Labuhanbatu, 2026)
This study aims to initiate the implementation of e-commerce using CMS Prestashop as a strategy to increase the sales index of Esteh Indonesia on Jalan Jendral Ahmad Yani, Rantauprapat. Data were obtained through observation and interviews with Esteh Indonesia staff to understand buying and selling activities and customer preferences. Although Prestashop offers easy online transactions, most customers prefer to order through drop shipping services or buy directly at outlets. The main factor influencing this is the level of customer trust in well-known local brands. Prestashop has great potential in expanding the market and increasing operational efficiency, but to achieve success, intensive promotion and socialization strategies are needed. With the right approach, a combination of technology and strengthening customer trust can encourage the implementation of Prestashop, thereby increasing sales and strengthening Esteh Indonesia's position in the local market